2022
DOI: 10.1039/d2tc00859a
|View full text |Cite
|
Sign up to set email alerts
|

Anti-counterfeiting applications by photochromism induced modulation of reversible upconversion luminescence in TiO2:Yb3+,Er3+ ceramic

Abstract: Photochromism-induced reversible upconversion luminescence modulation has received an extension attention due to its promising applications in anti-counterfeiting, optical storage, and switches. In this work, photochromic TiO2:Yb3+, Er3+ ceramics was prepared...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
26
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(26 citation statements)
references
References 38 publications
0
26
0
Order By: Relevance
“…Stimuli-responsive luminescent materials, with a specific response to external stimuli such as light, 1 pressure, 2 solvent molecules, 3 and heat, 4,5 have attracted extensive research interest and have shown wide application potentials in information storage, [6][7][8] chemical sensing, [9][10][11] and anti-counterfeiting. [12][13][14][15] In particular, thermosensitive materials are praised for their simple heating device requirement, highlighting their applications in thermal imaging, and thermometers.…”
Section: Introductionmentioning
confidence: 99%
“…Stimuli-responsive luminescent materials, with a specific response to external stimuli such as light, 1 pressure, 2 solvent molecules, 3 and heat, 4,5 have attracted extensive research interest and have shown wide application potentials in information storage, [6][7][8] chemical sensing, [9][10][11] and anti-counterfeiting. [12][13][14][15] In particular, thermosensitive materials are praised for their simple heating device requirement, highlighting their applications in thermal imaging, and thermometers.…”
Section: Introductionmentioning
confidence: 99%
“…17 Rare-earth ion incorporation in an optically silent lattice can successfully activate photoluminescence properties and can be helpful in designing new luminescent materials. 16,18,19 Since they involve parity forbidden f-f transitions, noncentrosymmetric site occupation is important to display electric dipole moment-induced intense emission. 15,20 These phosphors exhibit sharp emission spectra, large Stokes shifts, long lifetime of photoexcited electrons, and high photostability.…”
Section: Introductionmentioning
confidence: 99%
“…However, these authentication approaches are difficult and expensive. Thus, a variety of photochromic nanomaterials, such as upconversion nanoparticles, supramolecular scaffolds and polymer dots have been created to offer security-encoding ink media with the ability to produce anticounterfeiting patterns (Cheng et al, 2020;Haider et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…However, these authentication approaches are difficult and expensive. Thus, a variety of photochromic nanomaterials, such as upconversion nanoparticles, supramolecular scaffolds and polymer dots have been created to offer security‐encoding ink media with the ability to produce anticounterfeiting patterns (Cheng et al, 2020; Haider et al, 2022). Photochromism is an attractive technique for a range of products like optical data storage, displays and memories, ophthalmic lenses, sensors, and smart packaging (Abou‐Melha, 2022; Lin et al, 2019).…”
Section: Introductionmentioning
confidence: 99%